Analysis of Factors Affecting the Production of Independent Oil Palm Farming in Bayung Lencir District, Musi Banyuasin Regency - Napitupulu, Dompak; Effran, Endy; Anistia Sari, Firli (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
The production of oil palm is influenced by various production factors. This study aims to: (1) describe the general characteristics of independent oil palm farming in Bayung Lencir District, Musi Banyuasin Regency; and (2) analyze the production factors affecting its yield. The research was conducted from March 1 to April 21, 2025, in three villages: Wonorejo (highest production), Pangkalan Bayat (moderate production), and Mendis Jaya (lowest production). A quantitative method was applied using the Cobb-Douglas production function in logarithmic form, analyzed with multiple linear regression. Primary and secondary data were collected through interviews and documentation. A total of 62 farmers were selected using random sampling. The independent variables analyzed were land area (X1), plant age (X2), labor (X3), NPK fertilizer (X4), and pesticides (X5). The results show that independent oil palm farming in Bayung Lencir District is mostly conducted on privately owned land, averaging 3 hectares, with an average plant age of 7 years, indicating a productive phase. The average production reached 13.7 tons of fresh fruit bunches (FFB) per hectare per year. Regression analysis yielded an adjusted R² of 0.93, indicating that 93% of production variation is explained by the independent variables. Partially, land area, plant age, labor, and NPK fertilizer significantly affected production, while pesticides showed no significant effect.